2017
DOI: 10.1017/rdc.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic CO2in the Dakar (Senegal) Urban Area Deduced from14C Concentration in Tree Leaves

Abstract: Radiocarbon (14C) in atmospheric CO2 for the Dakar (Senegal) urban area was measured using tree leaves collected by botanists from 1900 to 2003. The aim of our study was to compare the local Suess effect in Dakar to the global one during the 20th century. The ∆14C of atmospheric CO2 in this region decreased from 1900 to 1958 during the pre-bomb era (–2±5‰ to –22±4‰). From 1958 to 1964, nuclear bomb tests injected a large amount of artificial 14C into the atmosphere, reflected in the rise of ∆14C values. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…It helps to diagnose carbon pathways from the atmosphere to the deep ocean including the biological carbon pump (e.g., Jasper and Hayes, 1990;Popp et al, 1989;Freeman and Hayes, 1992) and assists reconstruction of oceanic carbon cycling and even plankton cell size and community structure (e.g., Tuerena et al, 2019;Lorrain et al, 2020). For example, anthropogenic carbon emissions have a distinctly low δ 13 C content, making δ 13 C a useful property for tracing anthropogenic carbon throughout the Earth system (Eide et al, 2017;Levin et al, 1989;Ndeye et al, 2017). Atmospheric δ 13 C CO 2 has decreased from −6.5 ‰ in preindustrial times to −8.4 ‰ presently (Rubino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It helps to diagnose carbon pathways from the atmosphere to the deep ocean including the biological carbon pump (e.g., Jasper and Hayes, 1990;Popp et al, 1989;Freeman and Hayes, 1992) and assists reconstruction of oceanic carbon cycling and even plankton cell size and community structure (e.g., Tuerena et al, 2019;Lorrain et al, 2020). For example, anthropogenic carbon emissions have a distinctly low δ 13 C content, making δ 13 C a useful property for tracing anthropogenic carbon throughout the Earth system (Eide et al, 2017;Levin et al, 1989;Ndeye et al, 2017). Atmospheric δ 13 C CO 2 has decreased from −6.5 ‰ in preindustrial times to −8.4 ‰ presently (Rubino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These studies generally used deciduous plant leaves, specifically Ginkgo biloba L., Zea mays L., Agropyron repens (L.) Gould, Ficus sp., Setaria viridis (L.) P. Beauv. samples and past studies have shown a low but detectable 14 C dilution close to densely populated areas (Hsueh et al 2007;Riley et al 2008;Zhou et al 2014;Park et al 2015;Ndeye et al 2017).…”
Section: Introductionmentioning
confidence: 82%
“…Increasing anthropogenic carbon dioxide emissions into the atmosphere due to the combustion of large amounts of fossil fuel combustion has changed the local and global carbon cycle. The impact of these carbon dioxide emissions on the isotopic concertation in trees (tree rings and foliage) is evident (Suess 1955;Molnar et al 2007;Hua et al 2013;Pazdur et al 2013;Baydoun et al 2015;Ndeye et al 2017). The physiological processes of trees, such as their photosynthesis rate and stomatal conductance, can be affected not only by carbon dioxide, but also by other air contaminants, gases, and dust associated with human activities, such as industrial processes, road transport, and low and high-stack emissions (Staszewski et al 1994).…”
Section: Introductionmentioning
confidence: 99%